2018
DOI: 10.1007/978-1-4939-7816-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Intracellular Amyloidosis in Bacteria with RepA-WH1, a Prion-Like Protein

Abstract: Bacteria are the simplest cellular model in which amyloidosis has been addressed. It is well documented that bacterial consortia (biofilms) assemble their extracellular matrix on an amyloid scaffold, yet very few intracellular amyloids are known in bacteria. Here we describe the methods we have resorted to characterize in Escherichia coli cells the amyloidogenesis, propagation and dynamics of the RepA-WH1 prionoid. This prion-like protein, a manifold domain from the plasmid replication protein RepA, itself cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…His-SOD1 G93A-mCherry fibrilization was induced by adding SOD1 A4V aggregates produced in bacteria. Briefly, SOD1 A4V protein aggregates were induced in BL21 cells, bacteria cell pellet was collected, lysed, and centrifuged/resuspended for 5 cycles (Molina- García et al, 2018). Then a sucrose discontinuous gradient was prepared: in a 2 mL Eppendorf tube, successively was displayed 200 mL of 60 (bottom)> 50 > 40 > 30 > 20% (top) sucrose, freezing each layer at À80 C before adding the next one.…”
Section: Stable Cell Line Construction: Lentivirus Infection and Selementioning
confidence: 99%
“…His-SOD1 G93A-mCherry fibrilization was induced by adding SOD1 A4V aggregates produced in bacteria. Briefly, SOD1 A4V protein aggregates were induced in BL21 cells, bacteria cell pellet was collected, lysed, and centrifuged/resuspended for 5 cycles (Molina- García et al, 2018). Then a sucrose discontinuous gradient was prepared: in a 2 mL Eppendorf tube, successively was displayed 200 mL of 60 (bottom)> 50 > 40 > 30 > 20% (top) sucrose, freezing each layer at À80 C before adding the next one.…”
Section: Stable Cell Line Construction: Lentivirus Infection and Selementioning
confidence: 99%
“…Samples were run in duplicate: one set for Coomassie blue staining, and the other for Western blotting. Transference to PVDF membranes was carried out by semi-dry blotting, followed by blocking in TTBS plus powder milk, as described [51]. Primary antibodies were used at 1:20,000 dilution, either mouse anti-His (Sigma) or rabbit anti-mCherry (Abcam), then incubated with HRP-conjugated secondary anti-mouse/rabbit antibodies at 1:20,000 (Sigma).…”
Section: Protein Solubility Assaysmentioning
confidence: 99%
“…Amyloidogenesis assays in vitro were carried out as described [51]. Two mL Eppendorf tubes were set-up with 50 µL of 25µM RepA-WH1(A31V) in fibril assembly buffer (0.1M Na 2 SO 4 , 4 mM MgSO 4 , 20 mM Hepes•NaOH pH 8.0, 7% PEG4000, 3% MPD).…”
Section: Optogenetic Seeding Of Repa-wh1(a31v) Amyloidogenesis In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…This regulation is also critical for the replication of plasmidderived, bacteriophage-like or virus-like DNA genomes (Ruiz-Masó et al, 2015). Reps are essential for the replication of multidrug-resistant bacteria in humans (Schumacher et al, 2014) and studies have suggested that Reps have a role in transmissible amyloid proteinopathy (Molina-García et al, 2018;Giraldo et al, 2016Giraldo et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%